2021
DOI: 10.7759/cureus.17897
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Personality Traits on the Quality of Life of Health Professionals in COVID-19 Reference Hospital

Abstract: Introduction and objectivesCoronavirus disease 2019 has affected the quality of life of both general population and the healthcare workers and has increased the psychopathology levels. The objective of this research was to study the personality traits and the quality of life of healthcare professionals during the COVID-19 pandemic, in order to organize and apply interventions for the well-being of the staff. Materials and methodsThe study sample consisted of 400 healthcare workers, in Thoracic Diseases Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…These findings are supported by many previous studies conducted during the pandemic. 5,12,14,30 This study has several important implications. For one, it was the first to conduct an LPA to investigate potential profile groups among medical students based on the Big Five personality traits and coping strategies in the COVID-19 context.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These findings are supported by many previous studies conducted during the pandemic. 5,12,14,30 This study has several important implications. For one, it was the first to conduct an LPA to investigate potential profile groups among medical students based on the Big Five personality traits and coping strategies in the COVID-19 context.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, in crises such as COVID-19, high neuroticism may experience more negative emotions or stress than other groups of students. 9 , 12 , 13 Therefore, it is necessary to carefully examine the students’ psychological state in the maladaptive group, provide student support programs such as counseling and meditation, and train positive coping strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a survey conducted among Sotiria Hospital staff found that the young ones and the males exhibited a better quality of life and suggested interventions such as mindfulness and setting up teams to share experiences in supporting staff during the pandemic [ 18 ]. Also, another research at the same hospital found that health professionals mechanistically dehumanize the patient, while secure attachment acts protectively against self-dehumanization [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, resilience mediates this relationship and acts protectively on quality of life levels [ 12 ]. Furthermore, a study that took place in Sotiria Hospital in 2021 revealed that the quality of life of healthcare professionals has been affected by COVID-19 [ 18 ]. Substantial evidence supports the effectiveness of resilience to preserve psychological and mental health among hospital workers during the current pandemic [ 19 ].…”
Section: Introductionmentioning
confidence: 99%